Distributional income effects of banking regulation in Europe - Lars Brausewetter; Melina Ludolph; Lena Tonzer (Halle Institute for Economic Research (IWH), 2023)
We study the impact of stricter and more harmonized banking regulation along the income distribution using household survey data for 25 EU countries. Exploiting country-level heterogeneity in the implementation of European Banking Union directives allows us to control for confounders and identify effects. Our results show that these regulatory reforms aimed at increasing financial system resilience affected households heterogeneously. More stringent regulation reduces income growth for low-income households due to employment exits. Yet it tends to increase growth rates at the top of the distribution both for employee and self-employed income.
urn:nbn:de:gbv:3:2-1029756
Keywords: D31; G21; G28; G50; 330; distributional effects; EU-SILC microdata; financial regulation; income inequality